2010
DOI: 10.5042/bjfp.2010.0424
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term care needs in male medium security

Abstract: Medium secure units were designed to treat patients for up to three years, but some patients spend longer in acute medium secure settings which in general do not have a 'longer term focus'. The aim of this investigation was to assess and describe the needs of these patients. A survey questionnaire was designed and sent to responsible clinicians who had patients admitted at least five years previously to the Three Bridges Medium Secure Unit (males) in West London. Carer ratings using the Camberwell Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…Information on patient characteristics prior to this period is now likely to be obsolete. In putting our findings in the context of the wider literature we therefore draw particularly on Brown et al, 37 Jacques et al, 38 Shah et al 42 and Wilkes. 97 We also refer to Knapp et al, 86 Harty et al, 18 Ricketts et al 92 and Thomas et al, 29 despite their study dates, owing to unique aspects of relevance (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Information on patient characteristics prior to this period is now likely to be obsolete. In putting our findings in the context of the wider literature we therefore draw particularly on Brown et al, 37 Jacques et al, 38 Shah et al 42 and Wilkes. 97 We also refer to Knapp et al, 86 Harty et al, 18 Ricketts et al 92 and Thomas et al, 29 despite their study dates, owing to unique aspects of relevance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of different security levels and the time of this study (1999), again, limits the meaningfulness of any comparisons. Studies using our cut-off point of 5 years for LoS in medium secure care in England reported figures of 10% 82 (based on an admission sample at one unit), 21% 38 (based on a cross-sectional survey in one unit) and 9.3% 42 (based on a discharge sample in one unit). Some of these figures seem lower than ours, which can be attributed to methodological factors as described above; it is also of note that the units in these studies were NHS rather than independent provider units; the one with the higher figure had opened a ward specifically addressing the needs of a long-stay group.…”
Section: The Long-stay Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In England, research has found an average LoS in high secure care of eight years (Dell, Robertson, & Parker, 1987), and for medium secure care it is a little over two years (Edwards, Steed, & Murray, 2002). However, some authors have described a trend for patients to stay for five years or more (Rutherford & Duggan, 2007;Shah et al, 2011;Jacques, Spencer, & Gilluley, 2010) with around a third of medium secure patients deemed to need long-term care (Melzer et al, 2004). A more recent cross-sectional study identified that around 16% of patients resident in high secure settings in England had been resident for more than 10 years, and around 3% for more than 20 years (Völlm, 2015).…”
Section: Factors Associated With Length Of Stay Forensic Long-stay Inmentioning
confidence: 99%